2021
DOI: 10.31635/ccschem.020.202000403
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Shaped Polyoxometalate Built by {Mn 4 PW 9 } and PO 4 Units for Efficient Visible-Light-Driven Hydrogen Evolution

Abstract: A novel mixed-valence, ring-shaped multinuclear Mn-containing polyoxometalate, [H 2 N(CH 3 ) 2 ] 15 NaH 8 -[Mn III 3 Mn IV (μ 3 -O) 3 (OAc)PO 4 (B-α-PW 9 O 34 )] 4 • 36H 2 O (1) was made and systematically characterized using various spectroscopic and computational techniques. Its polyoxoanion can be described as a tetramer made of four [Mn III 3 Mn IV (μ 3 -O) 3 (OAc) (B-α-PW 9 O 34 )] 3− ({Mn III 3 Mn IV (PW 9 )}) clusters and four PO 4 linkers. Significantly, this structurally new complex 1 can efficiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…The Fourier transform infrared spectra and the XPS data (Figures S13b, S14b, and S15) showed that their crystal structures were maintained, highlighting the remarkable stability of the composites under photocatalytic conditions. According to the experimental results presented above and the literature, a possible reaction mechanism for this visible light-driven H 2 evolution process is proposed (Figure S16).…”
Section: Resultsmentioning
confidence: 80%
“…The Fourier transform infrared spectra and the XPS data (Figures S13b, S14b, and S15) showed that their crystal structures were maintained, highlighting the remarkable stability of the composites under photocatalytic conditions. According to the experimental results presented above and the literature, a possible reaction mechanism for this visible light-driven H 2 evolution process is proposed (Figure S16).…”
Section: Resultsmentioning
confidence: 80%
“…Polyoxometalate clusters (POMs) are a series of highly charged and oxygen-enriched structures with sizes between that of single atoms and conventional nanocrystals. They have attracted extensive attention in recent years because they show excellent performance in catalytic, electrocatalytic, , photocatalytic, , and medical fields. POM clusters can participate in the growth processes of nanostructures with greatly different assembly behaviors than the way of inorganic entities like metal oxide/sulfide.…”
Section: Introductionmentioning
confidence: 99%
“…Both possess wheel-shaped structures, and especially 2 is a rare double-wheel cluster. To our knowledge, the wheel-shaped POT species are mainly concentrated on single-wheel clusters, such as POMs with different shapes and dimensions {P 8 W 48 }, {As 4 W 40 }, {P 6 W 39 }, {Se 6 W 36 }, {Zr 6 Si 3 W 30 }, {Ti 8 Si 4 W 40 }, {Fe 48 P 16 W 96 }, {Fe 16 P 8 W 48 }, {Pd 10 Se 10 W 52 }, {Fe 8 P 4 W 40 }, {Ni 24 P 4 W 36 }, {Ru 4 As 4 W 40 }, {Mn 16 P 8 W 36 }, and so on. Clearly, double-wheel-shaped POTs have not been reported before the newly discovered 2 .…”
Section: Introductionmentioning
confidence: 99%